Pengembangan Modul Ajar Berdiferensiasi Berbasis Project-Based Learning untuk Meningkatkan Kreativitas Murid pada Materi Sel Kelas VIII di SMPN 1 Banyuasin III - Herri Cappri; Wulandari Saputri; Saleh Hidayat (EduInovasi: Journal of Basic Educational Studies, 2026)
In the 21st century, creativity is one of the most essential competencies for students. However, at SMPN 1 Banyuasin III, students’ creativity remains low. Although the Merdeka Curriculum supports 21st-century skills, the teaching materials used have not yet implemented differentiated modules based on Project Based Learning (PjBL). This study aimed to develop a differentiated PjBL-based teaching module on cell material to enhance students’ creativity in classes VIII.G and VIII.H. The research applied the 4D model (define, design, develop, disseminate). Data were collected through interviews, questionnaires, and observations, and analyzed using normality, homogeneity, and t-tests. The define stage revealed that both teachers and students needed a differentiated PjBL-based module to support creative thinking. The design stage produced cognitive creativity test items and the module framework. In the develop stage, the module achieved “very good” feasibility ratings in language (95.83%), content (88.23%), teaching materials (97.27%), and learning tools (92.72%), while the evaluation aspect was categorized as good (80%). The creativity test consisted of 10 valid items with high reliability (Cronbach’s Alpha = 0.80). Limited trials indicated the module was practical and easy to use. Effectiveness testing through pretest–posttest showed homogeneous data (Sig. 0.452) and a significant difference (0.000 < 0.05), indicating that the differentiated PjBL-based module significantly improved students’ creativity compared to conventional modules.